(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2025)
This study analyzes Patricia McCormick’s novel Sold using Critical Discourse Analysis, specifically employing "Building Tasks" by James Paul Gee and "Social Actor Theory" by Theo Van Leeuwen. Both theories aim to interpret discourses through a critical lens. The study examines the use of language in the text and suggests that the author has employed an Americanized perspective when portraying non-Western people, places, and cultures. It asserts that the author has activated a Westernized mentality while shaping the novel, potentially politicizing her notion of the superiority of Westerners and the inferiority of Easterners. The study concludes that such linguistic representations significantly maintain power, dominance, and social inequality in non-Western regions.